The farmer's son : calving season on a family farm - Connell, John, 1986- (Houghton Mifflin Harcourt, 2019)
"For fans of The Shepherd's Life, a poignant memoir -- and #1 Irish bestseller -- about a wayward son's return home to his family's farm, and how he found a new beginning in an age-old world. Farming has been in John Connell's family for generations, but he never intended to follow in his father's footsteps. Until, one winter, after more than a decade away, he finds himself back on the farm. Connell records the hypnotic rhythm of the farming day -- cleaning the barns, caring for the herd, tending to sickly lambs, helping the cows give birth. Alongside the routine events, there are the unforeseen moments when things go wrong: when a calf fails to thrive, when a sheep goes missing, when illness breaks out, when an argument between father and son erupts and things are said that cannot be unsaid. The Farmer's Son is the story of a calving season, and the story of a man who emerges from depression to find hope in the place he least expected to find it. It is the story of Connell's life as a farmer, and of his relationship with the community of County Longford, with his faith, with the animals he tends, and, above all, with his father." --